Citizen Perspective on M-Governance and Ethical Challenges in Bangladesh - Das, Rajib Chandra; Ruma, Israt Jahan (Transpublika Publisher, 2025)
E-governance enhances public services, lowers corruption, and encourages state modernization. In a rapidly developing nation like Bangladesh, an e-government is not only a symbol of modernity but also a strategic tool for attaining the Sustainable Development Goals and inclusive economic growth. Bangladesh is in the vanguard of the least developed countries’ digital transformation thanks to the government’s Smart Bangladesh (Vision 2041) plans, which seek to accelerate the shift to digital public services. Despite improvements in internet services and communication networks, Bangladesh is predicted to remain the least developed nation in the UN E-Government Development Index by 2026. Additionally, the government launched services for mobile government, or m-government. Mobile phones are used by these services to facilitate transactions and provide information. For instance, users can use SMS or mobile apps to check their test results, pay bills, and get notifications from the government. In Bangladesh, where computer ownership is low but cell phone penetration is strong, this strategy is very helpful. To facilitate cashless transactions, the government collaborated with mobile banking service companies. For bill payment, money transfers, and business transactions, services like bKash, Nagad, and Rocket gained popularity. However, citizens face severe ethical difficulties with these services. This study examines the ethical issues surrounding the M-governance experience, namely mobile financial services. Finally, it suggests methods for embedding ethics at all levels of M-governance, such as strong data security legislation, digital literacy and equity initiatives, interconnected platforms, and ethical bureaucratic stewardship.